2011
DOI: 10.3892/ol.2011.418
|View full text |Cite
|
Sign up to set email alerts
|

Copy number changes of CRISP3 in oral squamous cell carcinoma

Abstract: Abstract. The aim of this study was to identify tumor suppressor genes (TSGs) in oral squamous cell carcinoma (OSCC) using whole-genome analysis of microarray technology and real-time quantitative polymerase chain reaction (QPCR). We applied whole-genome analysis of TSGs in the specimens from 3 patients of OSCC by microarray technology. A total of 11 genes, CRISP3, SCGB3A1, AGR2, PIP, C20orf114, TFF1, STATH, AZGP1, MUC7, DMBT1 and LOC389429, were found to be down-regulated, and 2, matrix metallopeptidase (MMP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Notably, we find that miR-433 inhibits OSCC cell invasion and migration in the present study. Previously we observed that the MMP1 and MMP9 are up-regulated in OSCC, both of which belong to the MMP family and are responsible for the degradation of extracellular matrix components to promote cell metastasis [29][30][31]. Our study verified that miR-433 significantly suppressed the protein expression of MMP1 and MMP9.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, we find that miR-433 inhibits OSCC cell invasion and migration in the present study. Previously we observed that the MMP1 and MMP9 are up-regulated in OSCC, both of which belong to the MMP family and are responsible for the degradation of extracellular matrix components to promote cell metastasis [29][30][31]. Our study verified that miR-433 significantly suppressed the protein expression of MMP1 and MMP9.…”
Section: Discussionsupporting
confidence: 90%
“…Mixed results have been reported for a few of these DEGs in other contexts. For example, high expression of the cysteine-rich secretory protein CRISP3 (down 130-fold in NuKO cells) has been found in certain subtypes of prostate cancer [ 116 ] but down-regulation has been associated with oral squamous cell carcinoma [ 117 ]. A similar pattern has been found for the JCHAIN component of IgA and IgM (down 75-fold), which is up-regulated in prostate [ 108 ] but down-regulated in colorectal cancer [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Down-regulation of this defense molecule in our results indicate that the inactivation of CRISP3 can be an early event able to anticipate the occurrence of cutaneous lesions. Down-regulation of CRISP3 was also detected in Squamous Cell Carcinoma skin cancer [37].…”
Section: Discussionmentioning
confidence: 99%